Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Pertumbuhan Ekonomi dan Kemiskinan di Provinsi Nusa Tenggara Timur - Marianus Manek; Rudi Badrudin (Telaah Bisnis, 2017)
Abstract This study aims to analyze the influence of local revenue and equalization fund on the economic growth and the poverty of regencies/cities in the East Nusa Tenggara Province. Sample in this study consists of 21 regencies/cities in the East Nusa Tenggara Province. The type of data used in this study is secondary data, time series and cross-sectional data of regencies/cities since 2007 to 2016. Data are examined by using SEM-based variant named WarpPLS. The results of this study indicate that the local revenue had significant positive effect on economic growth, local revenue had significant negative effect on poverty, equalization fund had no significant negative effect on economic growth and poverty, and economic growth had no significant negative effect on poverty.